KARAKTERISASI KOMPOSIT POLIURETAN DENGAN PENGISI (FILLER) MIKRO KARBON AKTIF DARI CANGKANG KELAPA: Actived Carbon - Pada Mulia Raja (Jurnal Agro Fabrica, 2020)
Polyurethane is a type of polymer made by reacting polyol (OH) groups with isocyanate (NCO) groups. Thepurpose of this study was to determine the mechanical properties of a mixture of polyol and toluene sourcesas well as by adding the composition of activated carbon of palm shell as a filler to determine the best results.The materials used in making composites are PPG (Polypropylene Glycol), TDI (Toluent DiIsocyanate) andPalm Oil Shell Activated Carbon. Palm shells are carbonated at 600 ◦C, then made into powder using a ballmill and then sieved with 110 mesh particle sieve and activated using 10% H2SO4. FurthermorePolyurethanes are made by mixing, PPG (Polypropylene Glycol), TDI (Toluent in Isocyanate) with a ratio of60%: 40% and then added the activated carbon of palm oil shell as a filler with polyurethane: 95% activecarbon (P1), 90 %: 10% (P2), 80%; 20% (P3), and 75%: 25% (P4), then the functional group (FT-IR) andmechanical properties testing consisted of tensile strength and elasticity values. The results of thecharacterization of amine (NH), methyl groups (C-H3), Acetyl groups (CN), carbonyl groups (C = O),isocyanate groups (N = C = O), and Aromatic Rings (C = C) . This can be concluded after the addition ofactivated carbon palm shell does not cause chemical reactions in the functional group. While the results of thecharacterization of the tensile strength of P0 to P1 with a value of 0.1966 MPa to 0.0317 MPa, then increasedin the composition of 90 P2, P3, and P4 with values of 0.0985 MPa, 0.2318 MPa, 0.2981MPa, and finallyoccurred decrease again in the composition of P5. While the highest elasticity value on composites with aratio of P4 is 0.05196 MPa, while the lowest elasticity value on the composition of P5 with a value of 0.0475MPa.